Efeitos de dieta hiperproteica sobre a composição corporal e o metabolismo de ratos wistar adultos obesos - SOUSA, Rosângela Maria Lopes de (2018)
Introduction: The consumption of added sugars has been considered a global public health concern because of its implicit association with the epidemic of obesity, type 2 diabetes mellitus (DM2) and metabolic syndrome (MS). In this context, dietary manipulation is a primary factor in the control and prevention of obesity and its comorbidities. Many of the approaches prioritized low-fat and/or low-carbohydrate interventions. On the other hand, current studies have suggested high protein diets to promote greater weight loss and metabolic outcomes. Objective: To investigate the effects of a high-protein diet against sucrose-induced metabolic dysfunction in rats from weaning to adulthood, as well as to compare the metabolic benefits between increased protein intake and excess sugar removal. Material and Methods: Weaned male Wistar rats were randomly divided into two groups: control rats, fed a normal chow and obese rats (HS/HS), fed a high sucrose chow, for a period of 20 weeks. Subsequently, the HS/HS animals were randomly distributed into three new groups: rats kept on the HS diet; rats initially submitted to the HS diet and then replaced by normal food; and those replaced by a high protein diet (HS/HP). All groups were followed by an additional 12- week nutritional intervention. The following groups were evaluated: body weight, energy consumption, development of obesity, glycemic/lipid profile, glucose tolerance, insulin resistance, adipose tissue morphometry, skeletal muscle and liver, lipolytic activity, liver histology and biochemical profile of function liver. Results: Post-weaning exposure to the HS diet leads to the phenotype of metabolic syndrome in adulthood, characterized here by central obesity, glucose intolerance, dyslipidemia and insulin resistance. In addition, the HP diet was effective in reversing the damage caused by sugar consumption, marked by weight loss and obesity reduction with decreased fat mass. Replacing HS with the standard food also resulted in decreased adipose tissue accumulation, although to a lesser degree than that brought about by the HP diet. Notably, the HP diet restored the responsiveness of adipose tissue to the adrenergic agonist, making the tissue susceptible to lipolysis. Sucrose withdrawal attenuates the deleterious effects on the glucose-insulin axis. However, its replacement by the HP diet promoted the same effects, but improved glucose tolerance and insulin sensitivity. Finally, exposure to HS led to liver steatosis without inflammation, with a consequent elevation of ALT activity. However, both nutritional interventions were able to restore these changes. Conclusion: Our dataset shows that the HP diet has always re-established sucrose-induced metabolic outcomes. On the other hand, simply withdrawing high sucrose consumption also improves metabolic damage, although less pronounced. Thus, both nutritional interventions are mutually effective, potentially helping to treat patients with metabolic syndrome.